Penerapan Mikoriza dan Fosfor dalam Meningkatkan Produktivitas serta Mutu Fisiologis Galur Harapan Kacang Panjang (Vigna sinensis L.): Penelitian - Salmaa Ramadhani Putri; Asih farmia; Elea Nur Aziza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the effect of mycorrhizal dosing and phosphorus fertilization on the productivity and physiological quality of the long bean Hope line. The research was carried out using a factorial randomized block design (RAK) consisting of two factors, namely mycorrhizal dose (0, 5, and 10 g/plant) and phosphorus fertilization dose (0, 10, and 20 g/plant), which was repeated three times. The parameters observed consisted of the number of flowers per plant, the average number of fruit bunches, the dry weight of the pods, the water content and the germination capacity. Data analysis was carried out using variance analysis (ANOVA) at the 5% level, and if there was a real effect, it was continued with the least significant difference test (DMRT) at the 5% level. The research results showed that the combination of mycorrhizal doses at the level of 10 g/plant and phosphorus fertilizer at the level of 20 g/plant gave positive results in increasing growth, yield and physiological quality of plants. Thus, the integrated application of mycorrhiza and phosphorus can be an effective innovation and strategy to increase the productivity of long bean hope lines.